Student factors, theoretical comprehension, professional support, and peer support as predictors of fourth-year nursing students' clinical competence - Soputri, Nilawati (Cavite Adventist International Institute of Advanced Studies, 2008)
The main purpose of this study was to investigate how student factors, theoretical comprehension, professional support from clinical instructors (CIs) and staff nurses (SNs), and peer support, correlated with the predicted the 4th-year nursing students’ clinical competence (NSCC). The study used the descriptive correlational survey design. Three hundred sixty-four participants were selected by stratified random sampling method. They responded to the Career Development Interest Inventory. Nursing Clinical Teacher Effectiveness Inventory, Staff Nurse Supportive Scales, Nursing Students’ Peer Supportive Scales, and demographic profiles. The 4th-year nursing students’ theoretical comprehension (NSTC) was measured by their theoretical grade, while NSCC was measured by the clinical grade of related learning experiences.

The result of the study showed that students perceived support from CIs at the level of 5.4, SNs at the level 5.2, and peers at the level of 6.2 out of a 7-item scale. The mean of NSTC was 84.8%, and the level if NSCC was at the level of 88.1%.

There were significant differences in the variables of study when grouped by demographic characteristics and vocational personality. However, the differences were only small and may not be meaningful for implications. Positive medium correlation occurred between NSCC and NSTC, CIs’ support and SNs’ support, CIs’ support and peer support, and SNs support and peer support.

The best predictor of NSCC was NCTC ( = 0.50, R² = 0.25). The other predictors were enterprising vocational personality ( = 0,10, R² = 0.10), and peer support ( = 0,10, R² = 0.01). Since in the clinical area nursing students apply theory into practice, it is suggested for nursing educators to ensure that students have enough theoretical comprehension before they enter the clinical area. In addition, it is also essential for nursing educators to cultivate mutual support among nursing students, since students do learn from their peers. Further research may probe other factors such as the quality of nursing theory, student preparedness for clinical area, and facilities of nursing schools and health care agencies where students practice.
Dissertation (Doctor of Philosophy in Education - Curriculum and Institute) -- Adventist International Institute of Advanced Studies, June 2008.
Bibliography: leaves 234-245.
Keywords: Nursing students -- Counseling of; Clinical competence